2017
DOI: 10.1109/jtehm.2017.2722998
|View full text |Cite
|
Sign up to set email alerts
|

A New Wavelet-Based ECG Delineator for the Evaluation of the Ventricular Innervation

Abstract: T-wave amplitude (TWA) has been proposed as a marker of the innervation of the myocardium. Until now, TWA has been calculated manually or with poor algorithms, thus making its use not efficient in a clinical environment. We introduce a new wavelet-based algorithm for the delineation QRS complexes and T-waves, and the automatic calculation of TWA. When validated in the MIT/BIH Arrhythmia database, the QRS detector achieved sensitivity and positive predictive value of 99.84% and 99.87%, respectively. The algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The QRS complex detection algorithm had at least 96% sensitivity and positive predictivity for QRS complex detection and classification. The accuracy of the QRS delineation and measurement algorithm was close to the interobserver variation in the expert cohort responses, similar to that of existing single-lead ECG methods [33] , and similar to documented differences in QRSd results between clinical ECG machines and manual clinician measurements [34] . The QRSd measurement algorithm clinical classification accuracy was 95% in the 20 native conduction validation studies, which is better than the reported classification agreement between clinical ECG machines and doctors [34] .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The QRS complex detection algorithm had at least 96% sensitivity and positive predictivity for QRS complex detection and classification. The accuracy of the QRS delineation and measurement algorithm was close to the interobserver variation in the expert cohort responses, similar to that of existing single-lead ECG methods [33] , and similar to documented differences in QRSd results between clinical ECG machines and manual clinician measurements [34] . The QRSd measurement algorithm clinical classification accuracy was 95% in the 20 native conduction validation studies, which is better than the reported classification agreement between clinical ECG machines and doctors [34] .…”
Section: Discussionsupporting
confidence: 75%
“…No previously published QRS complex detection and/or classification algorithms for MECGs were found in the literature. Reported sensitivity and positive predictivity for single-lead ECG algorithms are usually over 99% for QRS complex detection without morphologic classification [15] , [33] . Fully automated real-time QRS detectors with morphologic classification (i.e., PVC detectors), however, tend to have positive predictivity and sensitivity values closer to 90% to 95% [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a post-processing is needed to remove such R peaks from RsR pattern or a fake R-peak due to a half ECG beat in a window. We set a threshold of the shortest period between each R peak from two successive QRS complexes, which is from 100 ms [7] to 250 ms [17]. The experimental results showed that 100 ms window is too small if there is a RsR pattern in a wide QRS complex and 250 ms is too large to a small QRS complex.…”
Section: A Detection Of R Peakmentioning
confidence: 99%
“…The results and the comparison with the literature are given in Table III. Finally, we built a record-by-record classification as proposed in [5] and more recently in [17] for T peak detection. We chose the same threshold in [5] to compare with the previous works.…”
Section: Detection Of T Peakmentioning
confidence: 99%
See 1 more Smart Citation